A qualitative analysis of the effect of a community-based primary health care programme on reproductive preferences and contraceptive use among the Kassena-Nankana of northern Ghana. Issue 1 (December 2016) - Dalaba, Maxwell; Stone, Allison; Krumholz, Abigail; Oduro, Abraham; Phillips, James; Adongo, Philip
Abstract Background In 2000, Ghana launched the Community-based Health Planning and Services (CHPS) initiative to improve access to health and family planning services. This initiative was based in part on research, known as the Navrongo Project, conducted in the Kassena-Nankana district (KND) between 1994 to 2003 which demonstrated significant impact on fertility and child mortality. This paper examines current contraceptive perceptions in communities that were exposed to the Project's service models over the 1994 to 2003 period, and the post-experimental policies of the CHPS era. Methods Qualitative study was conducted in the KND of Ghana from June to September, 2012, by convening 8 male and 8 female FGD panels as well as 8 in-depth interviews of community leaders. Data collection was stratified by original experimental cell of the Navrongo Project to permit appraisal of social effects of contrasting experimental conditions. Inductive content analysis was performed with QSR Nvivo 10 to identify predominant themes. Results While findings show that exposure to community-based services was associated with enhanced approval of birth spacing and limitation, this view is grounded in perceptions that childhood survival has improved. Nonetheless, concerns were expressed about contraceptive side effects, prominently permanent sterility. Strategies for male outreach and community engagement originally introduced during the Navrongo Project have not been sustained with CHPS scale-up. The apparent atrophy of attention to the needs of men may explain the resistance of some males to the notion of female reproductive autonomy and the practice of some women to adopt contraception in secret. Despite this apparent programmatic dearth of male engagement, there is evidence to suggest that social impact of the original male engagement strategy persists in communities where male mobilization was combined with doorstep provision of family planning care during the Navrongo Project. Conclusion Community-based services fostered attitudinal change towards family planning in a traditional sub-Saharan African setting. Sustained exposure to primary health care that have improved the survival of children has made the use of contraception more acceptable. Efforts should be embedded in primary health care programmes that address concerns about child survival while also consigning sustained priority to the information needs of men.